Problem of juridical evaluation of MGB agents combatant - Samulevičius, Saulius (Genocidas ir rezistencija, 2004)
This article focuses on the coordinated efforts of various authorities to investigate the cases of agents–hitmen, the difficulties encountered, and the ways of serving justice.
Keywords: repressive structures; agents; repressions; law